A comparative analysis of Passive Integrated Transponder (PIT) tagging in selective breeding programme of improved rohu (Jayanti) and catla - Avinash Rasal; Madhulita Patnaik; Khuntia Murmu; Jitendra Kumar Sundaray; Manohar Vasam; Jayant Kumar Swain; Kanta Das Mahapatra (Aquaculture Reports, 2022)
Passive Integrated Transponder (PIT) tags have been popularly used in identification of individual fish, stock, full-sib and half-sib families, year class and generations in aquaculture selective breeding programs. This study has been conducted on genetically improved Indian Major Carps (IMCs), improved rohu (Jayanti) and improved catla to compare PIT tagging of different size taggable fingerlings with respect to post tagging survival and tag retention. Six groups of improved rohu (Jayanti) and improved catla fingerlings with weight ranging from 10 to 150 g were tagged with PIT tags and mortality was recorded after 24 h. The overall mortality was thus found to be 3 % and 15 % in rohu and catla respectively. In rohu, 3 % mortality was observed after tagging in both small size fish (< 20 g) and large size fish (> 20 g) with no significant difference whereas in catla, mortality in small size fish (< 20 g) was 20 % compared to 14 % in large size fish (> 20 g) (p < 0.05). High correlation of length and weight with tagging space i.e, 0.96 and 0.91 respectively (p < 0.01) was found in rohu while the correlation of length and weight with tagging space was 0.96 and 0.88 respectively (p < 0.01) in catla. In rohu, the correlation of length, weight and tagging space on mortality % was − 0.142, − 0.145 and − 0.173 respectively but not significant (p > 0.05), whereas in catla the correlation of length, weight and tagging space on mortality % was − 0.508, − 0.510, − 0.500 respectively and significant (p < 0.05). Serum cortisol level in control and tagged rohu was 12.98 ± 1.58a ng/ml and 16.09 ± 0.55b ng/ml respectively while the level in control and tagged catla was 12.72 ± 1.56a and 15.97 ± 0.95b ng/ml respectively on the tagging day. There was no significant difference in serum cortisol level in control rohu and control catla and tagged rohu and tagged catla (p > 0.05). This study also revealed more sensitivity of the Indian major carp Labeo catla (Catla) to PIT tagging in comparison to Labeo rohita (rohu) and demonstrates the ideal size for PIT tagging in catla to be 20–30 g.